Physical and stressful psychological impacts of prolonged personal protective equipment use during the COVID-19 pandemic: A cross-sectional survey study - Giuseppe Candido; Costanza Tortù; Chiara Seghieri; Riccardo Tartaglia; Chiara Baglioni; Paolo Citti; Ida Marina Raciti; Micaela La Regina; Silvia Simonini; Moira Urbani; Chiara Parretti; Paul Barach (Journal of Infection and Public Health, 2023)
Background: Healthcare workers (HCWs) caring for COVID-19 infected patients are exposed to stressful and traumatic events with potential for severe and sustained adverse mental and physical health consequences. Our aim was to assess the magnitude of physical and mental health outcomes of HCWs due to the prolonged use of personal protective equipment (PPE) treating COVID-19 patients. Methods: This cross-sectional study assessed the symptoms of stress, anxiety, insomnia, and psychological resilience using the Stress and Anxiety to Viral Epidemics (SAVE) scale, Insomnia Severity Index (ISI), and Resilience Scale (RS), respectively, in Italy between 1st February and 31st March 2022. The physical outcomes reported included vertigo, dyspnea, nausea, micturition desire, retroauricular pain, thirst, discomfort at work, physical fatigue, and thermal stress. The relationships between prolonged PPE use and psychological outcomes and physical discomforts were analyzed using Generalized Linear Models (GLMs). We calculated the factor mean scores and a binary outcome to measure study outcomes. Findings: We found that 23% of the respondents reported stress related symptoms, 33% anxiety, 43% moderate to severe insomnia, and 67% reported moderate to very low resilience. The GLMs suggested that older people (>55 years old) are less likely to suffer from stress compared to younger people (<35 y.o); conversely, HCW aged more than 35 years are more inclined to suffer from insomnia than younger people (<35 y.o). Female HCW reported a lower probability of resilience than males. University employed HCWs were less likely to report anxiety than those who worked in a community hospital. The odds of suffering from insomnia for social workers was significantly higher than for other HCWs. Female HCW>3 years old, enrolled in training programs for nursing, social work, technical training and other healthcare professionals increased the probability of reported physical discomforts. HCW that worked on non COVID-19 wards and used PPE for low-medium exposure level, were at lower risks for lasting physical side effects as compared to the HCW who worked in high-risk PPE intense, COVID-19 environments. Interpretation: The study suggests that frontline HCWs who had extensive PPE exposure while directly engaged in the diagnosis, treatment, and care for patients with COVID-19 are at significant risks for lasting physical and psychological harm and distress.